Charging properties of thin gate dielectrics, obtained by the method of rapid thermal processing - Kovalchuk, Natalya S.; Marudo, Yuliya A.; Omelchenko, Anna A.; Pilipenka, Uladzimir A.; Saladukha, Vitali A.; Demidovich, Sergey A.; Kolos, Vladimir V.; Anishchik, Victor M.; Filipenia, Viktar A.; Shestovski, Dmitry V. (Journal of the Belarusian State University. Physics, 2022)
The charge properties of thin dielectrics, obtained by rapid thermal processing (RTP), and their interfaces with silicon for MOS transistors are investigated. The production of insulator layers was carried out by a two- or three-stage RTP with photon processing regimes similar for each stage (duration – 12 s, maximum temperature – 1250 °C). After the third stage of RTP in a nitrogen atmosphere of the gate oxides, obtained by a two-stage process in oxygen atmosphere, the defects responsible for local charge centers are partially eliminated. There is also an increase in the relative value of the surface potential by an average of 100 relative units. The elimination of defects is a consequence of the rearrangement of the structure of the dielectric, its interface with silicon, and the diffusion of oxygen and silicon atoms along the interface of the insulator layer. For samples obtained by a two-stage RTP in an oxygen atmosphere and subjected to the third stage of processing in a forming gas, there is an almost complete elimination of local charge centers and an increase in the relative value of the surface potential by an average of 300 relative units. In this case, in addition to the processes occurring during the treatment of SiO2 by the RTP method in an nitrogen atmosphere, the liquidation of charge centers is a consequence of the passivation of defects by hydrogen atoms.
Keywords: gate dielectric; rapid thermal processing; three-stage process; surface potential